Dynamic Selective Exposure during Decision-Making. Issue 4 (1st October 2016) - Phillips, James G.; Hoon, Teressa; Landon, Jason
ABSTRACT: To understand dynamic changes in the likelihood that people would access and selectively expose themselves to information online, the present study examined the checking of account balances during simulated gambling. Sixteen participants played 120 hands of computer Blackjack for points, at higher or lower levels of risk (different point multipliers), and after each win or loss the computer recorded if participants checked their account balances. There were individual differences in checking rates. Participants who were more likely to check balances exhibited a selectivity of exposure to decision consonant information after a win at low risk. Although it was expected that people would seek to maintain positive mood, data were better explained in terms of Cognitive Dissonance. The effects of Cognitive Dissonance are liable to extend beyond single static decisions into dynamic online environments.